2012
DOI: 10.1166/jnn.2012.6370
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Physicochemical Characterization and Bioavailability of Nano-Liposomes Formed by Mixing Lipids at Different Ratios

Abstract: Liposomes are small lipid vesicles that mimic biological membranes and have been spotlighted in the clinical field due to their ability to enclose a biologically active substance of any structure and to release it into the host's body. This study compares the physicochemical properties and biological activity of nano-liposomes with different compositions to determine the most effective formulation for further in vivo application. Nano-scale liposomes composed of different ratios of 1,2-dimyristoyl-sn-glycero-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This affects the van der Waals interactions between the hydrocarbon chains and increases their mobility. [ 62 ] Most of the phospholipid bilayers have a transition temperature between 40 and 70 °C. [ 63 ] SONL prepared by ultrasonication method had a T g of 57.3 °C.…”
Section: Resultsmentioning
confidence: 99%
“…This affects the van der Waals interactions between the hydrocarbon chains and increases their mobility. [ 62 ] Most of the phospholipid bilayers have a transition temperature between 40 and 70 °C. [ 63 ] SONL prepared by ultrasonication method had a T g of 57.3 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The immunological responses were examined by using the newly formed nano-liposomes via porcine interferon gamma (IFN-γ) enzyme-linked immunospot (ELISPOT) assay in peripheral blood mononuclear cells (PBMC) of immunocompetent pigs. The porcine IFN-γ ELISPOT assay results revealed that DMPE/DCP most potently induced the IFN-γ secretion by PBMC, followed by DMPE/DCP/Chol and DMPE [ 27 ]. Liposomes based on phospholipids used as adjuvant and adjuvant carrier in various microbial diseases caused by different type of microorganisms, including P. malarie [ 28 ], Influenza Virus (INFLEXAL ® V) [ 29 ], HAV (Epaxal ® ) HIV [ 30 ], and ICMV P. vivax [ 28 ].…”
Section: Types Of Various Nanomaterials Used In Veterinary Medicinmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38] Elucidation of actual structural features of such small assemblies, especially smaller than 100 nm and more specifically in the sub-10 nm scales, has been possible (to some extent) by development of analytical tools for extracting geometrical signatures from indirect data measurements (e.g., molecular diffraction patterns 7 27 and application of techniques such as fluorescence resonance energy transfer 39 ). In general, pattern generation and recognition in 3-D space have been of wide interest in the area of molecular structures.…”
Section: Discussionmentioning
confidence: 99%